2020
DOI: 10.1075/ssol.20007.chl
|View full text |Cite
|
Sign up to set email alerts
|

Fact or fiction?

Abstract: Many studies have claimed to find that reading fiction leads to improvements in social cognition. But this work has left open the critical question of whether any type of narrative, fictional or nonfictional, might have similar effects. To address this question, as well as to test whether framing a narrative as fiction matters, the current studies presented participants (N = 268 in Study 1; N = 362 in Study 2) with literary fiction texts, narrative nonfiction texts, expository nonfiction texts, or no texts. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Research comparing the effects of fiction and nonfiction on social cognition frequently confounds up to three variables: fictionality (whether or not something is real), social content (whether or not the content focuses on people), and narrativity (whether something is written in expository or narrative form). To the best of our knowledge, the only experimental study that explicitly pitted narrative versus expository texts found no effect of narrativity (Chlebuch et al, 2020). Other experiments compare the effects of (narrative) fiction versus expository nonfiction (e.g., Black & Barnes, 2015a;, thus confounding form with fictionality.…”
Section: Fictionality Versus Social Contentmentioning
confidence: 88%
See 2 more Smart Citations
“…Research comparing the effects of fiction and nonfiction on social cognition frequently confounds up to three variables: fictionality (whether or not something is real), social content (whether or not the content focuses on people), and narrativity (whether something is written in expository or narrative form). To the best of our knowledge, the only experimental study that explicitly pitted narrative versus expository texts found no effect of narrativity (Chlebuch et al, 2020). Other experiments compare the effects of (narrative) fiction versus expository nonfiction (e.g., Black & Barnes, 2015a;, thus confounding form with fictionality.…”
Section: Fictionality Versus Social Contentmentioning
confidence: 88%
“…Research examining the effects of merely labeling a written stimulus "fiction" versus "nonfiction" has found no effect on transportation, or engagement with the story (Green & Brock, 2000), or on empathic understanding and subsequent prosocial behavior (Koopman, 2015). Chlebuch et al (2020) found no effect of framing on RMET performance across two studies, and although labeling fiction as fiction resulted in lower scores on a text-based assessment of social-cognitive ability in one of two studies, there was no effect of labeling nonfiction in either.…”
Section: Fictionality Versus Social Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, two central issues remain unresolved. The first is the robustness of these findings in view of multiple failed replications and studies with null results (see, e.g., Chlebuch et al, 2020; Lenhart & Richter, 2022; Panero et al, 2016; Samur et al, 2018; Wimmer, Currie, et al, 2021, 2022). Second, a capacity for high levels of empathy and ToM is generally considered desirable (e.g., A.…”
Section: Psychological Effects Of Reading Fictionmentioning
confidence: 92%
“…However, two central issues remain unresolved. The first is the robustness of these findings in view of multiple failed replications and studies with null results (see, e.g., Chlebuch et al, 2020;Samur et al, 2018;Wimmer, Currie, et al, 2021, 2022. Second, a capacity for high levels of empathy and ToM is generally considered desirable (e.g., A. M. Ferguson et al, 2021;Goldstein & Winner, 2012) and research confirming that reading fiction has robust positive effects on these capacities is likely to be welcomed.…”
Section: Empathy and Theory Of Mind (Tom)mentioning
confidence: 94%